2003
DOI: 10.14411/eje.2003.018
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of the damselflies, Coenagrion mercuriale and Ceriagrion tenellum (Odonata: Coenagrionidae), at their northern range margins, in Britain

Abstract: Abstract. Emergence of Coenagrion mercuriale and Ceriagrion tenellum was examined in a mixed population at their northern range margin in Britain. Mortality at emergence was quantified in C. mercuriale. Consistent with their larval diapause characteristics, both species had an asynchronous emergence pattern, typical of "summer" species. Daily emergence of C. mercu riale was positively correlated with the duration of sunlight on the previous day (controlling for season) and its emergence period was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In central Europe the majority of the preferred prey species of bee-eaters (Hymenoptera and Odonata, Krebs and Avery 1985;Arbeiter et al 2014) generally emerge from March onwards and reach their maximum abundances in mid-July until mid-August (e.g., Purse and Thompson 2003;Oertli et al 2005). Our study during this peak time revealed no temporal variation in insect availability during the months of high summer season (May-July) but spatial differences among habitat types with higher counts at the hedgerow and arable land (Fig.…”
Section: Availability Of Aerial Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In central Europe the majority of the preferred prey species of bee-eaters (Hymenoptera and Odonata, Krebs and Avery 1985;Arbeiter et al 2014) generally emerge from March onwards and reach their maximum abundances in mid-July until mid-August (e.g., Purse and Thompson 2003;Oertli et al 2005). Our study during this peak time revealed no temporal variation in insect availability during the months of high summer season (May-July) but spatial differences among habitat types with higher counts at the hedgerow and arable land (Fig.…”
Section: Availability Of Aerial Insectsmentioning
confidence: 99%
“…However, there is no clear evidence for an adjustment of reproduction to the peak food abundance (Dunn et al 2011), probably due to unpredictable food supply during the nestling period (Cucco and Malacarne 1996b;Dunn et al 2011). Beeeaters cannot adjust laying in prospects of more favourable weather, because insect abundance can vary from day to day and will seasonally decrease in August (Purse and Thompson 2003;Oertli et al 2005). In addition, the late arrival and long nestling period allows only raising a single clutch per season (Lessells and Avery 1989).…”
Section: Breeding Success and Nestling Conditionmentioning
confidence: 99%
“…Jakob & Suhling (1999) have shown that strong wind can damage dragonflies during emer-gence. Deformity of soft wings condemns odonates to death or to lower reproductive success (Purse & Thompson 2003). One idea is that the level of wind disturbance in certain forest (similar to wetlands) would be heterogeneous, i.e.…”
mentioning
confidence: 99%
“…The question of whether habitat selection at emergence differs between sexes has been raised in this study. One unusual finding is that body size increased with the emergence season; a result that is rarely found in previous studies (Banks & Thompson 1985;Inden-Lohmar 1997;Purse & Thompson 2003). Sugimura (1983) showed an increasing trend in body size in Deiela phaon from Japan; however, the sample size was too small.…”
Section: Discussionmentioning
confidence: 68%